Answer:
2nd - (w - 5)(w + 5)
4th - (-4v - 9)(-4v + 9)
Step-by-step explanation:
1. The first option shows an expression multiplied by its opposite(x -1), so therefore, it does not show the difference of squares
2. The second option does show the difference of squares because it is in the form (a + b)(a - b)
3. The third option is just a square because the same expression is multiplied by itself.
4. The fourth option is the difference of squares because it is in the form (a + b)(a - b). a equals -4v and b equals 9 in this case.
5. The fifth option is not the difference of squares. No term in common in both expressions
6. The sixth option is just a square because the same expression is multiplied by itself.
In all, there are two options that are the difference of squares, the 2nd and 4th.
Answer:
10=y/11-13
We move all terms to the left:
-10-(y/11-13)=0
-y/11+13-10=0
We multiply all the terms by the denominator
-y+13*11-10*11=0
We add all the numbers together, and all the variables
-1y+33=0
We move all terms containing y to the left, all other terms to the right
-y=-33
y=-33/-1
y=+33
Answer:
16
Step-by-step explanation: